Etiología de las podredumbres radicales de plántulas de QUERCUS SPP. Y PINUS HALEPENSIS EN VIVEROS FORESTALES DE ANDALUCÍA - Andicoberry, S.; LORA, F.; SÁNCHEZ, E.; Trapero, A. (III Congreso Forestal Español, 2001)
A disease surey carried out during 1998-99 showed that holm oak (Quercus ilex) and Aleppo pine (Pinus halepensis) seedlings were affected by damping-off and root rot in three forest nurseries in Andalucía, southern Spain. A similar problem was detected affecting four species of Quercus (Q. coccinea, Q. faginea, Q. ilex, and Q. suber) in a forest nursery in 2000. Three species of Phytophthora (P. cinnamomi, P. cryptogea, and P. drechsleri) were isolated from holm oak feeder roots, and P. drechsleri was isolated from feeder roots of Aleppo pine in the first survey in 1998-99. In the second survey, Cylindrocarpon didymum was isolated from the feeder roots of the four Quercus spp. essayed, and C. destructans was isolated only from Q. faginea. Pathogenicity tests were conducted using 1 year-old healthy plants of cork oak, holm oak and Aleppo pine. Isolates of the three Phytophthora species were pathogenic to the three host species, inducing root rot and plant death. Holm oak was the most susceptible host and P. cinnamomi was the most virulent species. Isolates of Cylindrocarpon were pathogenic to cork oak and holm oak causing root rot, yellowing, defoliation, and plant death.
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español pub-location: Granada
Keywords: Cylindrocarpon; Phytophthora; Quercus coccinea; Quercus faginea; Quercus ilex; Quercus suber

Etiología de las podredumbres radicales de plántulas de QUERCUS SPP. Y PINUS HALEPENSIS EN VIVEROS FORESTALES DE ANDALUCÍA - Andicoberry, S; LORA, F; SÁNCHEZ, E; TRAPERO, A (III Congreso Forestal Español, 2001)
A disease surey carried out during 1998-99 showed that holm oak (Quercus ilex) and Aleppo pine (Pinus halepensis) seedlings were affected by damping-off and root rot in three forest nurseries in Andalucía, southern Spain. A similar problem was detected affecting four species of Quercus (Q. coccinea, Q. faginea, Q. ilex, and Q. suber) in a forest nursery in 2000. Three species of Phytophthora (P. cinnamomi, P. cryptogea, and P. drechsleri) were isolated from holm oak feeder roots, and P. drechsleri was isolated from feeder roots of Aleppo pine in the first survey in 1998-99. In the second survey, Cylindrocarpon didymum was isolated from the feeder roots of the four Quercus spp. essayed, and C. destructans was isolated only from Q. faginea. Pathogenicity tests were conducted using 1 year-old healthy plants of cork oak, holm oak and Aleppo pine. Isolates of the three Phytophthora species were pathogenic to the three host species, inducing root rot and plant death. Holm oak was the most susceptible host and P. cinnamomi was the most virulent species. Isolates of Cylindrocarpon were pathogenic to cork oak and holm oak causing root rot, yellowing, defoliation, and plant death.
Keywords: Cylindrocarpon; Phytophthora; Quercus coccinea; Quercus faginea; Quercus ilex; Quercus suber